Prevalence of Sarcoptes scabiei Infection in Pet Dogs in Southern China - Yi-Zhou Chen; Guo-Hua Liu; Hui-Qun Song; Rui-Qing Lin; Ya-Biao Weng; Xing-Quan Zhu (The Scientific World Journal)
Little is known about the prevalence of Sarcoptes scabiei infection in pet dogs in China. In the present study, the prevalence of S. scabiei infection in pet dogs in Guangzhou, southern China, was investigated between January and December, 2009. A total of 3,977 pet dogs admitted to animal hospitals were examined for the presence of S. scabiei using a parasitological approach. The average prevalence of S. scabiei infection in pet dogs is 1.18% (95% confidence interval (CI): 0.85–1.52%). The prevalence of S. scabiei was higher in winter (1.42%; 95% CI: 0.29–2.55%), summer (1.39%; 95% CI: 0.83–1.96%), and autumn (1.1%; 95% CI: 0.53–1.68%) than in spring (0.63%; 95% CI: 0.02–1.25%). Furthermore, the prevalence of S. scabiei was the highest in Pekingese (21.88%; 95% CI: 7.55–36.2%), followed by Papillon (5.26%; 95% CI: 0–11.06%) and Bichon Frise (3.19%; 95% CI: 0–6.75%). The results of the present investigation indicate that S. scabiei infection is prevalent in pet dogs in Guangzhou, China, which provides relevant “baseline” data for conducting control strategies and measures against scabies in this region and elsewhere in China. To our knowledge, this is the first comprehensive report of S. scabiei prevalence in pet dogs in China.